IMPLEMENTASI KOMPONEN SISTEM FASILITAS TRANSPORTASI TERHADAP BATAS SRP DAN WAKTU TUNGGU LAYANAN KEBERANGKATAN DAN KE.docx - Rocky Abisai Benaya Sitorus; Hendri Dunant Hamidi (Universitas Negeri Jakarta, 2018)
One of the functions of a public transport terminal that has a function as a temporary stopover from road transport activities. Likewise with the function of the Pulo Gebang Integrated Terminal which has a function as a point transit and a temporary stop from road transportation activities for the AKAP Bus and the AKDP Bus. In carrying out its function as a terminal, safe, smooth and comfortable circulation is required. Start the bus in the position in front of the terminal door, or when the bus is in a position outside the terminal door. The smooth circulation of the terminal will have an impact on parking capacity and service waiting times, which in turn will result in the smooth departure and arrival of buses at the Pulo Gebang Integrated Terminal.In order to expedite the circulation of the activities of the arrival and departure of the AKAP Bus at the Pulo Gebang Integrated Terminal, needed problem solving is regarding the implementation of the SOP. AKAP Bus departures and arrivals. By the authors conducted research by collecting various kinds of research data while carrying out the Job Training (PKL) there. The data collection process was carried out by using various methods, such as: field observation techniques, interview techniques, and requests for permission to request data on the daily reports of AKAP Bus departures and arrivals. Then, the collected data is reviewed and it is hoped that it can become a solution for the performance in the Operational Unit and the Integrated Terminal Partnership Pulo Gebang in carrying out operational activities for the departure and arrival of the AKAP Bus.The results of this study found obstacles that occurred during the implementation process of the facility system component activities against the limit SRP and bus operational service time at the Pulo Gebang Integrated Terminal. This is supported by the daily data on the arrival and departure of the AKAP Bus at the Pulo Gebang Integrated Terminal.